Electrolyte for non-aqueous secondary battery and non-aqueous secondary battery using the same
The electrolytic solution with a specific organic solvent composition and lithium salts improves the charge-discharge cycle characteristics of non-aqueous secondary batteries using lithium-free transition metal sulfides as positive electrode materials, addressing capacity and cycle performance issues.
Patent Information
- Application Number
- JP2020187493
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-10
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-11-10
AI Technical Summary
Current lithium-ion secondary batteries have insufficient positive electrode capacity and poor charge-discharge cycle characteristics, particularly when using sulfur-based or lithium-free transition metal sulfides as active materials.
An electrolytic solution for non-aqueous secondary batteries containing a lithium-free transition metal sulfide as a positive electrode active material, with a specific composition of organic solvents (100% cyclic carbonate and 0-20% chain carbonate) and lithium salts, which improves charge-discharge cycle characteristics.
The solution enhances the charge-discharge cycle characteristics of non-aqueous secondary batteries, achieving higher capacity retention rates and efficiency.
Smart Images

Figure 0007599692000002 
Figure 0007599692000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolyte for a non-aqueous secondary battery and a non-aqueous secondary battery using the same. [Background technology]
[0002] In recent years, the increasing performance of portable electronic devices, hybrid vehicles, etc. has led to a demand for increasingly higher capacity lithium-ion secondary batteries used in them. However, current lithium-ion secondary batteries have insufficient capacity in the positive electrode compared to the negative electrode, and even lithium nickel oxide-based materials, which are said to have relatively high capacity, have a capacity of only about 190 to 220 mAh / g.
[0003] On the other hand, sulfur has a high theoretical capacity of approximately 1670 mAh / g, and is expected to be used as a positive electrode active material, but it is generally known that the capacity of sulfur-based positive electrode active materials decreases with repeated charge-discharge cycles. This is because sulfur dissolves into the organic electrolyte as lithium polysulfide during charging and discharging, so technology to suppress its dissolution into the organic electrolyte is essential.
[0004] Although non-lithium-containing transition metal sulfides (transition metal sulfides not containing lithium) have electronic conductivity and little elution into organic electrolyte, it is not sufficient. For example, vanadium sulfide is taken as an example of a non-lithium-containing transition metal sulfide. When crystalline vanadium sulfide (III) (V2S3) sold as a reagent is used as a positive electrode active material, the reaction with the organic electrolyte cannot be suppressed, and the actual measured capacity is only about 23 mAh / g charge capacity and 52 mAh / g discharge capacity. In contrast, the present inventors have reported that low-crystalline vanadium sulfide having a specific composition exhibits high capacity when used as an electrode active material for lithium ion secondary batteries, and also has excellent charge / discharge cycle characteristics (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2018 / 181698 Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, the inventors have developed a material that exhibits high capacity when used as an electrode active material for lithium ion secondary batteries and also has excellent charge-discharge cycle characteristics. However, there is a continuing demand for higher performance lithium ion secondary batteries, and further improvements in the charge-discharge cycle characteristics are required.
[0007] The present invention has been made in consideration of the current state of the prior art described above, and a main object of the present invention is to provide an electrolyte solution capable of improving the charge-discharge cycle characteristics in a non-aqueous secondary battery using a lithium-free transition metal sulfide as a positive electrode active material. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to achieve the above-mentioned object. As a result, they have found that, when the total amount of organic solvent contained in the electrolyte is 100 volume %, the content of the cyclic carbonate compound is 80 to 100 volume %, and the content of the chain carbonate compound is 0 to 20 volume %, the charge-discharge cycle characteristics can be further improved in a non-aqueous secondary battery using a lithium-free transition metal sulfide as a positive electrode active material. The present invention has been completed as a result of further research based on such findings. That is, the present invention includes the following configurations.
[0009] Item 1. A non-aqueous secondary battery electrolyte used in a non-aqueous secondary battery that uses a lithium-free transition metal sulfide as a positive electrode active material, The electrolyte solution contains an organic solvent containing a cyclic carbonate compound, and The nonaqueous secondary battery electrolyte contains a cyclic carbonate compound in an amount of 80 to 100% by volume and a chain carbonate compound in an amount of 0 to 20% by volume, based on 100% by volume of the total amount of the organic solvent.
[0010] Item 2. The nonaqueous secondary battery electrolyte according to Item 1, wherein the lithium-free transition metal sulfide is vanadium sulfide and / or molybdenum sulfide.
[0011] Item 3. The nonaqueous secondary battery electrolyte according to Item 1 or 2, wherein the cyclic carbonate compound is at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate.
[0012] Item 4. The nonaqueous secondary battery electrolyte according to any one of Items 1 to 3, wherein the chain carbonate compound is at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and methyl propyl carbonate.
[0013] Item 5. The nonaqueous electrolyte solution for a secondary battery according to any one of Items 1 to 4, further comprising a lithium salt.
[0014] Item 6. The nonaqueous electrolyte for a secondary battery according to Item 5, wherein the lithium salt is at least one selected from the group consisting of an organic lithium salt having a sulfonyl group, an inorganic lithium salt, and an organic lithium salt having a boron atom.
[0015] Item 7. The nonaqueous secondary battery electrolyte according to Item 5 or 6, wherein the lithium salt is at least one selected from the group consisting of lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(pentafluoroethanesulfonyl)imide (Li(C2F5SO2)2N), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium bis(oxalato)borate (LiBOB), lithium oxalatodifluoroborate (LiBF2(C2O4)), and lithium bis(malonate)borate (LiB(C3O4H2)2).
[0016] Item 8. The nonaqueous electrolyte solution for a secondary battery according to any one of Items 5 to 7, wherein the lithium salt has a concentration of 0.3 to 2.0 mol / L.
[0017] Item 9. The nonaqueous electrolyte solution for a secondary battery according to any one of Items 1 to 8, which is an electrolyte solution for a lithium ion secondary battery.
[0018] Item 10. A non-aqueous secondary battery comprising the non-aqueous electrolyte for secondary batteries according to any one of items 1 to 9.
[0019] Item 11. The nonaqueous secondary battery according to Item 10, which is a lithium ion secondary battery. Effect of the Invention
[0020] According to the present invention, in a non-aqueous secondary battery using a lithium-free transition metal sulfide as a positive electrode active material, the charge-discharge cycle characteristics can be further improved. [Brief description of the drawings]
[0021] [Figure 1] 1 shows the charge / discharge cycle characteristics (capacity retention rate) of lithium secondary batteries using the nonaqueous electrolyte solutions for secondary batteries of Examples 1 to 4 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] In this specification, "containing" is a concept that encompasses all of "comprise," "consist essentially of," and "consist only of." In addition, in this specification, when a numerical range is shown as "A to B," it means A or more and B or less.
[0023] In this specification, the concentration (mol / L) of each component means that the desired number of moles is contained per 1 L of organic solvent.
[0024] 1. Electrolyte for non-aqueous secondary batteries The non-aqueous secondary battery electrolyte of the present invention is an electrolyte for use in a non-aqueous secondary battery that uses a lithium-free transition metal sulfide as a positive electrode active material, and the electrolyte contains an organic solvent containing a cyclic carbonate compound, and the content of the cyclic carbonate compound is 80 to 100 volume % and the content of the chain carbonate compound is 0 to 20 volume %, relative to 100 volume % of the total amount of the organic solvent.
[0025] (1-1) Lithium-free transition metal sulfides In the present invention, as the transition metal sulfide, a lithium-free transition metal sulfide is used because those containing lithium need to be handled under an inert atmosphere such as an argon gas atmosphere. Such lithium-free transition metal sulfides are not particularly limited as long as they are lithium-free transition metal sulfides used as a positive electrode active material in a non-aqueous secondary battery in which the non-aqueous secondary battery electrolyte of the present invention is used, and are known as a positive electrode active material for lithium ion secondary batteries. Specifically, vanadium sulfide (lithium-free vanadium sulfide; International Publication No. 2018 / 181698), niobium sulfide and titanium niobium sulfide (lithium-free niobium sulfide and lithium-free titanium niobium sulfide; International Publication No. 2015 / 049986), molybdenum sulfide (lithium-free molybdenum sulfide), iron sulfide (lithium-free iron sulfide), and the like can be mentioned. The descriptions in WO 2018 / 181698 and WO 2015 / 049986 are incorporated by reference. These lithium-free transition metal sulfides can be used alone or in combination of two or more. Among these, vanadium sulfide (lithium-free vanadium sulfide; WO 2018 / 181698), molybdenum sulfide (lithium-free molybdenum sulfide), etc. are preferred from the viewpoints of charge / discharge capacity, charge / discharge cycle characteristics, etc., and vanadium sulfide (lithium-free vanadium sulfide; WO 2018 / 181698) is more preferred.
[0026] Such lithium-free transition metal sulfides may be either crystalline or low-crystalline (or amorphous) materials. Among them, low-crystalline (or amorphous) materials are preferred because they are particularly excellent in charge / discharge capacity and charge / discharge cycle characteristics, and are easily inhibited from reacting with an organic electrolyte when in contact with the organic electrolyte.
[0027] In the present invention, the lithium-free transition metal sulfide has a composition ratio of sulfur to transition metal (S / M 1) is preferably in a molar ratio of 2.1 to 10, from the viewpoints of being particularly excellent in charge / discharge capacity, charge / discharge cycle characteristics, etc., being easy to synthesize, and being easily inhibited from reacting with the organic electrolyte solution when it comes into contact with the organic electrolyte solution.
[0028] More specifically, the non-lithium-containing transition metal sulfide has the general formula (1): M 1 S x (1) [In the formula, M 1 represents a transition metal. x represents 2.1 to 10. It is preferable that the composition is represented by the formula: 1 When multiple transition metals are contained as sulfur, the composition ratio of sulfur to the total amount of transition metals (S / M 1 ) is preferably in a molar ratio of 2.1 to 10.
[0029] Thus, in the present invention, the non-lithium-containing metal sulfide is a transition metal (M 1 ) element ratio. Therefore, in the present invention, by using a lithium-free metal sulfide, it is possible to have a high charge / discharge capacity and excellent charge / discharge cycle characteristics. In the present invention, the higher the sulfur content (the larger x), the higher the charge / discharge capacity, and the lower the sulfur content (the smaller x), the less elemental sulfur is contained and the higher the charge / discharge cycle characteristics. In the present invention, even if a sulfide with poor charge / discharge cycle characteristics is used, the charge / discharge cycle characteristics can be improved by using an electrolyte solution with a composition described later, so that it is particularly useful to apply a polysulfide that is likely to have a high charge / discharge capacity but insufficient charge / discharge cycle characteristics. For this reason, x is preferably 2.1 to 10, more preferably 3 to 8.
[0030] Hereinafter, vanadium sulfide (lithium-free vanadium sulfide), which is a preferred lithium-free transition metal sulfide, will be described as an example.
[0031] In the present invention, the vanadium sulfide preferably has a crystal structure similar to that of crystalline vanadium(IV) tetrasulfide (VS4) (hereinafter sometimes referred to as "VS4 type crystal structure").
[0032] More specifically, vanadium sulfide preferably has peaks at 15.4°, 35.3°, and 45.0° with a tolerance of ±1.0° within the diffraction angle 2θ range of 10° to 80° in an X-ray diffraction diagram using CuKα radiation. In other words, it preferably has peaks in the ranges of 14.4° to 16.4°, 34.3° to 36.3°, and 44.0° to 46.0°.
[0033] In the present invention, the X-ray diffraction pattern is obtained by powder X-ray diffraction measurement (θ-2θ method) under the following measurement conditions: Measuring device: D8ADVANCE (BrukerAXS) X-ray source: CuKα40kV / 40mA Measurement conditions: 2θ=10°~80°, 0.1° step, scanning speed 0.02° / sec Measured at.
[0034] In the present invention, vanadium sulfide preferably has a peak at the 2θ position described above, but also preferably has a peak at at least one (particularly all) of 54.0° and 56.0° within the diffraction angle 2θ range of 10° to 80°, with an allowable range of ±1.0°.
[0035] In the present invention, vanadium sulfide is a sulfide having a high ratio of sulfur in the average composition, but sulfur is hardly present as elemental sulfur as described later, and is preferably bonded with vanadium to form a low-crystalline sulfide. In this way, in the present invention, vanadium sulfide has a low crystallinity, and by lowering the crystallinity, it is possible to have more sites into which lithium ions can be inserted and removed, and also to easily have gaps that can be three-dimensionally conductive paths for lithium. In addition, it has many advantages, such as being easily subjected to three-dimensional volume changes during charging and discharging. For this reason, it is possible to further improve the charge / discharge capacity and charge / discharge cycle characteristics. In addition, it is preferable that vanadium sulfide (such as V2S3) used as a raw material is hardly present. In this specification, the average composition of the sulfide refers to the element ratio of each element that constitutes the entire sulfide.
[0036] The "low crystallinity" in the present invention will be described below. In the present invention, it is preferable that the vanadium sulfide does not have peaks at 2θ=15.4°, 35.3°, and 45.0°, or even if a peak appears, the full width at half maximum of the peak is 0.8 to 2.0° (particularly 1.0 to 2.0°). In addition, in crystalline vanadium (IV) sulfide (VS4), the full width at half maximum of the peaks at 2θ=15.4°, 35.3°, and 45.0° is 0.2 to 0.6°. Thus, in the present invention, it is preferable that the vanadium sulfide does not have peaks at 2θ=15.4°, 35.3°, and 45.0°, or even if a peak appears, the full width at half maximum of the peak is larger than that of crystalline vanadium (IV) sulfide (VS4). In this way, since the low crystallinity of the present invention makes it easier to increase the number of sites where Li can exist stably, when the metal sulfide of the present invention is used as a positive electrode active material, it is easier to improve the charge / discharge capacity and charge / discharge cycle characteristics.
[0037] Furthermore, when a material containing a large amount of elemental sulfur or the like is used as a positive electrode active material, the cyclic carbonate compound contained in the electrolyte for a nonaqueous secondary battery of the present invention is likely to react with elemental sulfur. In contrast, in the present invention, for example, when mechanical milling is performed for a sufficient period of time, the above-mentioned vanadium sulfide contains almost no elemental sulfur or the like. Therefore, when used as a positive electrode active material, these problems do not occur even when a cyclic carbonate compound is used, and it is easy to dramatically improve the charge / discharge capacity and charge / discharge cycle characteristics.
[0038] More specifically, the strongest peak of sulfur (S8) is present at 2θ=23.0° within a tolerance range of ±1.0°. For this reason, in the X-ray diffraction pattern by CuKα radiation, it is preferable that there is no peak having a maximum at 2θ=23.0°, which is a peak characteristic of elemental sulfur, within a tolerance range of ±1.0°, or the area of the peak having a maximum at 2θ=23.0° is 20% or less (0 to 20%, particularly 0.1 to 19%) of the area of the peak having a maximum at 2θ=35.3°. As a result, in the present invention, the vanadium sulfide can be a material that contains almost no elemental sulfur, which reduces the concern of causing the reaction with the electrolyte as described above, and can further improve the charge / discharge capacity and charge / discharge cycle characteristics.
[0039] In the present invention, the vanadium sulfide preferably does not have peaks at 2θ=25.8° and 27.8°, which are peaks characteristic of elemental sulfur, or the area of the peak having a maximum at said positions is 10% or less (0 to 10%, particularly 0.1 to 8%) of the area of the peak having a maximum at 2θ=35.3°, within a tolerance range of ±1.0°. This allows the vanadium sulfide to be a material that contains almost no elemental sulfur, which reduces the concern of causing the above-mentioned reaction with the electrolyte, and further improves the charge / discharge capacity and charge / discharge cycle characteristics.
[0040] Vanadium sulfides that satisfy such conditions preferably have a strong peak at g(r)=2.4 Å within a tolerance of ±0.1 Å in X-ray / neutron atomic pair correlation function analysis (PDF analysis), but for sulfides with better charge / discharge capacity and charge / discharge cycle characteristics, it is more preferable to have a shoulder peak at g(r)=2.0 Å and more preferably a peak at g(r)=3.3 Å. In other words, vanadium sulfides preferably have not only VS bonds but also SS bonds (disulfide bonds).
[0041] In the present invention, the above-mentioned vanadium sulfide can be obtained, for example, by a production method using vanadium sulfide and sulfur as raw materials or intermediates, the production method including a step of subjecting the raw materials or intermediates to a mechanical milling method.
[0042] Mechanical milling is a method of grinding and mixing raw materials while applying mechanical energy. According to this method, the raw materials are ground and mixed by applying mechanical impact and friction, so that vanadium sulfide and sulfur come into vigorous contact with each other and are finely divided, causing a reaction of the raw materials. In other words, mixing, grinding, and reaction occur simultaneously. Therefore, it is possible to make the raw materials react more reliably without heating them to high temperatures. By using mechanical milling, a metastable crystal structure that cannot be obtained by normal heat treatment can be obtained.
[0043] Specifically, the mechanical milling treatment can involve mixed pulverization using a mechanical pulverizing device such as a ball mill, a bead mill, a rod mill, a vibration mill, a disk mill, a hammer mill, or a jet mill.
[0044] These raw materials or intermediates can be all mixed together and subjected to mechanical milling, or some of the materials or intermediates can be subjected to mechanical milling first, and then the remaining materials can be added and subjected to mechanical milling.
[0045] In particular, when producing vanadium sulfide with a high sulfur content (the composition ratio (S / V) of sulfur to vanadium is 3.3 or more in molar ratio), crystalline vanadium sulfide may be obtained depending on the charged mass. Therefore, in order to easily obtain low-crystalline vanadium sulfide with excellent charge / discharge capacity and charge / discharge cycle characteristics, it is preferable to first subject vanadium sulfide and a part of sulfur to mechanical milling treatment to obtain a desired low-crystalline sulfide as an intermediate, and then subject the obtained low-crystalline sulfide and the remaining sulfur to mechanical milling treatment.
[0046] As a specific raw material, it is preferable to use crystalline vanadium(III) sulfide (V2S3) as vanadium sulfide. There is no particular limitation on the vanadium sulfide, and any commercially available vanadium sulfide can be used. In particular, it is preferable to use a high-purity one. In addition, since the vanadium sulfide is mixed and pulverized by mechanical milling, there is no limitation on the particle size of the vanadium sulfide used, and usually, commercially available powdered vanadium sulfide can be used.
[0047] As for sulfur, elemental sulfur (S8) can be used in an amount necessary for forming a sulfide of a desired composition. There is no particular limitation on the sulfur used as a raw material, and any sulfur can be used. In particular, it is preferable to use sulfur of high purity. In addition, since the sulfur is mixed and pulverized by mechanical milling, there is no limitation on the particle size of the sulfur used, and commercially available powdered sulfur can usually be used.
[0048] Furthermore, as described above, when the mechanical milling process is performed in multiple steps (particularly in two steps), the intermediate product is a low-crystalline vanadium sulfide having a desired composition (low-crystalline VS 2.5 etc.) can also be used.
[0049] The mixing ratio of the raw materials can be the same as the element ratio of vanadium and sulfur in the target vanadium sulfide, since the ratio of the raw materials is almost the same as the ratio of each element in the product. For example, it is preferable to use 1.2 moles or more (particularly 1.2 to 17.0 moles, more preferably 3.0 to 13.0 moles) of sulfur per mole of vanadium sulfide.
[0050] The temperature at which the mechanical milling treatment is carried out is not particularly limited, but is preferably 300° C. or lower, more preferably −10 to 200° C., in order to make it difficult for sulfur to volatilize and to make it difficult for the previously reported crystal phase to be formed.
[0051] The time for the mechanical milling treatment is not particularly limited, and the mechanical milling treatment can be carried out for any time until the desired vanadium sulfide is precipitated.
[0052] The atmosphere in which the mechanical milling process is carried out is not particularly limited, but an inert gas atmosphere such as a nitrogen gas atmosphere or an argon gas atmosphere can be used.
[0053] For example, the mechanical milling treatment can be carried out within a treatment time range of 0.1 to 100 hours (particularly 15 to 80 hours). Note that this mechanical milling treatment can also be carried out in multiple steps with breaks in between, if necessary.
[0054] When the mechanical milling process is repeated multiple times, the above conditions can be applied to each mechanical milling process.
[0055] By the above-mentioned mechanical milling treatment, the target vanadium sulfide can be obtained as a fine powder.
[0056] (1-2) Organic Solvent As described above, the non-aqueous secondary battery electrolyte of the present invention is an electrolyte for non-aqueous secondary batteries that uses a lithium-free transition metal sulfide as a positive electrode active material. Thus, in the present invention, even though the electrolyte is used in a non-aqueous secondary battery that uses a lithium-free transition metal sulfide, the total amount of the organic solvent is taken as 100 volume %, and the content of the cyclic carbonate compound is 80 to 100 volume %, and the content of the chain carbonate compound is 0 to 20 volume %, thereby suppressing the reaction between the carbonate compound and the lithium-free transition metal sulfide, and dramatically improving the charge-discharge cycle characteristics.
[0057] The cyclic carbonate compound is not particularly limited as long as it can be used as an organic solvent in the electrolyte of a lithium ion secondary battery, and examples thereof include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, etc. These cyclic carbonate compounds can be used alone or in combination of two or more kinds.
[0058] The content of the cyclic carbonate compound is 80 to 100% by volume, preferably 85 to 100% by volume, and more preferably 90 to 100% by volume, based on the total amount of the organic solvent being 100% by volume. By setting the content of the cyclic carbonate compound within the above range, it is possible to dramatically improve the charge-discharge cycle characteristics in particular. In the present invention, only the cyclic carbonate compound can be used as the organic solvent (the content of the cyclic carbonate compound is 100% by volume), or other organic solvents such as chain carbonate compounds can be used in addition to the cyclic carbonate compound (the content of the cyclic carbonate compound is 80 to 99.9% by volume, particularly 85 to 99.8% by volume, and further 90 to 99.5% by volume). However, from the viewpoint of the charge-discharge cycle characteristics, it is preferable to use only the cyclic carbonate compound as the organic solvent (the content of the cyclic carbonate compound is 100% by volume).
[0059] The chain carbonate compound is not particularly limited as long as it can be used as an organic solvent in the electrolyte of a lithium ion secondary battery, and examples thereof include dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl propyl carbonate, etc. These chain carbonate compounds can be used alone or in combination of two or more kinds.
[0060] The content of the chain carbonate compound is 0 to 20% by volume, preferably 0 to 15% by volume, and more preferably 0 to 10% by volume, based on the total amount of the organic solvent being 100% by volume. By setting the content of the chain carbonate compound within the above range, it is possible to dramatically improve the charge-discharge cycle characteristics in particular. As described above, in the present invention, as the organic solvent, only a cyclic carbonate compound can be used (the content of the chain carbonate compound is 0% by volume), or a chain carbonate compound can be used (the content of the chain carbonate compound is 0.1 to 20% by volume, particularly 0.2 to 15% by volume, and further 0.5 to 10% by volume). From the viewpoint of easily suppressing the decomposition of the organic solvent, it is preferable that the content of the chain carbonate compound is small, and it is particularly preferable that only a cyclic carbonate compound is used as the organic solvent (the content of the chain carbonate compound is 0% by volume).
[0061] In the present invention, the organic solvent constituting the nonaqueous secondary battery electrolyte may be composed only of the above-mentioned cyclic carbonate compound and, if necessary, a chain carbonate compound, or may contain, in addition to these, a compound known as an organic solvent in the electrolyte of a lithium ion secondary battery.
[0062] Examples of such organic solvents as the third component include cyclic carboxylate compounds such as γ-butyrolactone, chain carboxylate compounds such as methyl acetate, methyl propionate, ethyl acetate, sulfone compounds such as sulfolane, diethylsulfone, ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,2-dimethoxyethane, etc. These organic solvents as the third component can be used alone or in combination of two or more kinds.
[0063] When the organic solvent is contained as the third component, the content of the organic solvent as the third component is preferably 0.1 to 10 volume %, and more preferably 0.2 to 5 volume %, based on 100 volume % of the total amount of the organic solvent, from the viewpoint of charge / discharge cycle characteristics.
[0064] (1-3) Lithium salt The non-aqueous secondary battery electrolyte of the present invention preferably further contains a lithium salt. The lithium salt is not particularly limited, and examples thereof include organic lithium salts having a sulfonyl group, inorganic lithium salts, and organic lithium salts having a boron atom.
[0065] The organic lithium salt having a sulfonyl group is not particularly limited as long as it is one that has been conventionally used in electrolytes for non-aqueous secondary batteries, and examples thereof include lithium trifluoromethanesulfonate (LiCF3SO3); organic lithium salts having a perfluoroalkanesulfonyl group (lithium bis(trifluoromethanesulfonyl)imide (LiTFSI; Li(CF3SO2)2N), lithium bis(pentafluoroethanesulfonyl)imide (Li(C2F5SO2)2N, etc.). Among these, from the viewpoint of withstanding charging at a higher voltage and further improving the charge / discharge cycle characteristics, organic lithium salts having a perfluoroalkanesulfonyl group are preferred, and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI; Li(CF3SO2)2N) is more preferred. These organic lithium salts having a sulfonyl group may be used alone or in combination of two or more.
[0066] The inorganic lithium salt is not particularly limited as long as it is one that has been used in the electrolyte for non-aqueous secondary batteries, and examples thereof include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), and lithium perchlorate (LiClO4). Among them, from the viewpoint of withstanding charging at a higher voltage and further improving the charge-discharge cycle characteristics, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and the like are preferred, and lithium hexafluorophosphate (LiPF6) is more preferred. These inorganic lithium salts may be used alone or in combination of two or more.
[0067] The organic lithium salt having a boron atom is not particularly limited as long as it is one that has been used in the electrolyte for non-aqueous secondary batteries, and examples thereof include lithium bis(oxalate)borate (LiBOB; LiB(C2O4)2), lithium oxalate difluoroborate (LiBF2(C2O4)), and lithium bis(malonate)borate (LiB(C3O4H2)2). Among these, lithium bis(oxalate)borate (LiBOB; LiB(C2O4)2) is preferred from the viewpoint of withstanding charging at a higher voltage and further improving the charge / discharge cycle characteristics. These organic lithium salts having a boron atom may be used alone or in combination of two or more.
[0068] As the lithium salt, since the nonaqueous secondary battery of the present invention uses a lithium-free metal sulfide as the positive electrode active material, in consideration of the effect on the charge-discharge cycle characteristics due to reactivity with sulfur, an organic lithium salt having a sulfonyl group is preferable, and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI; Li(CFSO)N) is more preferable.
[0069] In the nonaqueous secondary battery electrolyte of the present invention, the concentration of the lithium salt is not particularly limited, and is preferably 0.3 to 2.0 mol / L, more preferably 1.0 to 2.0 mol / L, from the viewpoint of charge / discharge cycle characteristics.
[0070] (1-4)Other In the non-aqueous secondary battery electrolyte of the present invention, components other than those described above, such as additives, can be contained within a range that does not impair the effects of the present invention (for example, 0.01 to 0.2 mol / L, particularly 0.02 to 0.1 mol / L). Examples of such additives include tetrabutylammonium hexafluorophosphate, tetrabutylammonium perchlorate, tetramethylammonium tetrafluoroborate, tetramethylammonium chloride, tetraethylammonium chloride, tetrabutylammonium chloride, tetramethylammonium bromide, tetraethylammonium bromide, tetrabutylammonium bromide, vinylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, vinylethylene carbonate, 1,3,2-dioxathiolane-2-oxide, 3-sulfolene, biphenyl, and trialkyl phosphates (such as trimethyl phosphate). These additives may be used alone or in combination of two or more.
[0071] The non-aqueous secondary battery electrolyte of the present invention is usually in liquid form, but a gel electrolyte gelled with a gelling agent made of a polymer or the like can also be used.
[0072] 2.Non-aqueous secondary battery The nonaqueous secondary battery of the present invention includes the above-mentioned electrolyte for nonaqueous secondary batteries. Other configurations and structures may be the same as those used in conventionally known nonaqueous secondary batteries. In general, the nonaqueous secondary battery of the present invention may include a positive electrode, a negative electrode, and a separator in addition to the above-mentioned electrolyte for nonaqueous secondary batteries.
[0073] (2-1) Positive electrode The positive electrode may have a configuration in which a positive electrode mixture layer containing a positive electrode active material, a binder, and the like is formed on one or both sides of a positive electrode current collector.
[0074] This positive electrode mixture layer can be produced through a process in which a binder is added to a positive electrode active material and a conductive assistant added as necessary, and the resultant is dispersed in an organic solvent to prepare a paste for forming the positive electrode mixture layer (in this case, the binder may be dissolved or dispersed in the organic solvent in advance), which is then applied to the surface (one side or both sides) of a positive electrode current collector made of a metal foil or the like, dried to form a positive electrode mixture layer, and processed as necessary.
[0075] The above-mentioned lithium-free metal sulfide is used as the positive electrode active material. The details of the lithium-free metal sulfide are the same as those described above.
[0076] As in the case of ordinary non-aqueous secondary batteries, the conductive assistant can be graphite, carbon black (acetylene black, ketjen black, etc.), amorphous carbon materials such as carbon materials having amorphous carbon formed on the surface, fibrous carbon (vapor-grown carbon fiber, carbon fiber obtained by spinning pitch and then carbonizing it, etc.), carbon nanotubes (various multi-layer or single-layer carbon nanotubes), etc. The conductive assistant for the positive electrode can be used alone or in combination of two or more kinds.
[0077] Examples of the binder include polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyacrylic acid, styrene butadiene rubber, polyimide, polyvinyl alcohol, and water-soluble carboxymethyl cellulose.
[0078] The organic solvent used in producing the positive electrode mixture is not particularly limited, and examples thereof include N-methylpyrrolidone (NMP), which can be made into a paste by using the organic solvent together with the positive electrode active material, a binder, and the like.
[0079] The composition of the positive electrode mixture layer is preferably, for example, about 70 to 95% by weight of the above positive electrode active material and about 1 to 30% by weight of the binder. When a conductive assistant is used, the composition is preferably about 50 to 90% by weight of the above positive electrode active material, about 1 to 20% by weight of the binder, and about 1 to 40% by weight of the conductive assistant. Furthermore, the thickness of the positive electrode mixture layer is preferably about 1 to 100 μm per side of the current collector.
[0080] The positive electrode current collector may be, for example, a foil, punched metal, expanded metal, or mesh made of aluminum, stainless steel, nickel, titanium, or an alloy thereof, and typically, an aluminum foil having a thickness of about 10 to 30 μm is preferably used.
[0081] (2-2) Negative electrode The negative electrode may have a configuration in which a negative electrode mixture layer containing a negative electrode active material, a binder, and the like is formed on one or both sides of a negative electrode current collector.
[0082] This negative electrode mixture layer can be produced by mixing the negative electrode active material, a conductive assistant which is added as necessary, and a binder, forming the mixture into a sheet, and then pressing the sheet onto the surface (one side or both sides) of a negative electrode current collector made of a metal foil or the like.
[0083] The negative electrode active material is not particularly limited, and examples thereof include graphite (natural graphite, artificial graphite, etc.), non-sinterable carbon, lithium metal, tin, silicon, and alloys containing these, SiO, etc. Preferably, lithium metal, lithium alloys, etc. can be used in metal lithium primary batteries and metal lithium secondary batteries, and materials capable of doping and dedoping lithium ions (graphite (natural graphite, artificial graphite, etc.), non-sinterable carbon, etc.) can be used as active materials in lithium ion secondary batteries. These negative electrode active materials may be used alone or in combination of two or more.
[0084] As in the case of ordinary non-aqueous secondary batteries, the conductive assistant can be graphite, carbon black (acetylene black, ketjen black, etc.), amorphous carbon materials such as carbon materials having amorphous carbon formed on the surface, fibrous carbon (vapor-grown carbon fiber, carbon fiber obtained by spinning pitch and then carbonizing it, etc.), carbon nanotubes (various multi-layer or single-layer carbon nanotubes), etc. The conductive assistant for the negative electrode can be used alone or in combination of two or more kinds, or can be omitted if the negative electrode active material has high conductivity.
[0085] Examples of the binder include polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyacrylic acid, styrene butadiene rubber, polyimide, polyvinyl alcohol, and water-soluble carboxymethyl cellulose.
[0086] The composition of the negative electrode mixture layer is preferably, for example, about 70 to 95% by weight of the above-mentioned negative electrode active material and about 1 to 30% by weight of the binder. When a conductive assistant is used, the composition is preferably about 50 to 90% by weight of the above-mentioned negative electrode active material, about 1 to 20% by weight of the binder, and about 1 to 40% by weight of the conductive assistant. Furthermore, the thickness of the negative electrode mixture layer is preferably about 1 to 100 μm per side of the current collector.
[0087] The negative electrode current collector may be, for example, a foil, punched metal, expanded metal, mesh, or net made of aluminum, copper, stainless steel, nickel, titanium, or an alloy thereof, and typically, a copper foil having a thickness of about 5 to 30 μm is preferably used.
[0088] (2-3) Separator The above-mentioned positive and negative electrodes can be used in the form of, for example, a laminated electrode body in which the electrodes are laminated with a separator interposed therebetween, or in the form of a wound electrode body in which the laminated electrode body is further wound in a spiral shape.
[0089] The separator should have sufficient strength and be capable of retaining a large amount of electrolyte. From this viewpoint, a microporous film or nonwoven fabric having a thickness of 10 to 50 μm and an opening ratio of 30 to 70% and containing one or more of polyethylene, polypropylene, ethylene-propylene copolymer, etc. is preferred.
[0090] The nonaqueous secondary battery of the present invention may be in the form of a tube (such as a rectangular tube or a cylindrical tube) using a stainless steel can or an aluminum can as an exterior can, or may be in the form of a soft package battery using a laminate film integrated with a metal foil as an exterior body. EXAMPLES
[0091] The present invention will be described in detail below based on examples. However, it goes without saying that the present invention is not limited to the following examples.
[0092] Synthesis Example 1: Synthesis of vanadium sulfide (positive electrode active material) Commercially available vanadium(III) sulfide (V2S3; manufactured by Kojundo Chemical Laboratory Co., Ltd.) and sulfur (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed in a glove box (dew point -80°C) in an argon gas atmosphere so that the molar ratio was 1:6, and the mixture was sealed in a glass tube in a vacuum. The vacuum-sealed sample was fired in a tubular furnace at 400°C for 5 hours. The fired sample was fired in a vacuum at 200°C for 8 hours to desulfurize the excess sulfur, and crystalline vanadium sulfide VS4 (c-VS4) was synthesized.
[0093] Next, the obtained crystalline VS4 (c-VS4) was subjected to mechanical milling (ball diameter 4 mm, rotation speed 270 rpm) for 40 hours in a ball mill (Fritsch PL-7) in an argon gas atmosphere glove box (dew point -80°C) to synthesize low-crystalline vanadium sulfide VS4 (a-VS4), which was used as the positive electrode active material.
[0094] Synthesis Example 2: Synthesis of molybdenum sulfide (positive electrode active material) Molybdenum sulfide was synthesized according to a method similar to that described in a previous report (X. Wang, K. Du, C. Wang, L. Ma, B. Zhao, J. Yang, M. Li, X. Zhang, M. Xue, and J. Chen, ACS Appl. Mater. Interface, 9, 38606-38611 (2017).).
[0095] Commercially available ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 A mixture of ammonium sulfide ((NH4)2S; Fujifilm Wako Pure Chemical Industries, Ltd.) and ion-exchanged water was added dropwise to the flask. The mixture was then kept at 50°C for 1 hour, and then at 90°C for 4 hours to obtain a precipitate. The precipitate was collected by filtration and dried under an Ar gas atmosphere for 12 hours. The dried sample was then heat-treated in an electric furnace in an Ar atmosphere at 220°C for 1 hour to obtain amorphous MoS. 5.7 was synthesized.
[0096] Example 1: LiTFSI / EC+PC Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added to a mixed solvent of ethylene carbonate (EC) and propylene carbonate (PC) (EC:PC=50:50 (volume ratio)) to a concentration of 1.0 mol / L (volume based on the solvent) to obtain a nonaqueous secondary battery electrolyte solution of Example 1.
[0097] Examples 2 and 5: LiTFSI / EC+PC Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added to a mixed solvent of ethylene carbonate (EC) and propylene carbonate (PC) (EC:PC=10:90 (volume ratio)) to a concentration of 1.0 mol / L (volume based on the solvent) to obtain nonaqueous secondary battery electrolyte solutions of Examples 2 and 5.
[0098] Example 3: LiPF 6 / EC+PC Lithium hexafluorophosphate (LiPF6) was added to a mixed solvent of ethylene carbonate (EC) and propylene carbonate (PC) (EC:PC = 50:50 (volume ratio)) to a concentration of 1.0 mol / L (volume based on the solvent) to obtain a non-aqueous secondary battery electrolyte solution of Example 3.
[0099] Example 4: LiTFSI / EC+PC+DMC Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added to a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC) and dimethyl carbonate (DMC) (EC:PC:DMC=40:40:20 (volume ratio)) to a concentration of 1.0 mol / L (volume based on the solvent) to obtain a nonaqueous secondary battery electrolyte solution of Example 4.
[0100] Comparative Examples 1 and 3: LiPF 6 / EC+DMC Lithium hexafluorophosphate (LiPF6) was added to a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) (EC:PC = 1:1 (volume ratio)) to a concentration of 1.0 mol / L (volume based on the solvent) to obtain a nonaqueous secondary battery electrolyte solution of Comparative Example 1.
[0101] Comparative example 2: LiTFSI / EC+DMC Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added to a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) (EC:PC=1:1 (volume ratio)) to a concentration of 1.0 mol / L (volume based on the solvent) to obtain a nonaqueous secondary battery electrolyte solution of Comparative Example 1.
[0102] Test example 1: Charge / discharge test VS4 powder obtained in Synthesis Example 1 (Examples 1 to 5 and Comparative Examples 1 and 2) or MoS obtained in Synthesis Example 2 5.7Using the positive electrode active material (Example 5 and Comparative Example 3) and the nonaqueous secondary battery electrolyte solutions obtained in Examples 1 to 5 and Comparative Examples 1 to 3, test electrochemical cells (lithium secondary batteries) were produced by the following method, and constant current charge / discharge measurements were performed for 50 cycles at 25° C., a charge / discharge rate of 0.1 C (1 C=747 mAh / g) within a voltage range of 2.6 to 1.5 V, and a rest time between cycles of 10 minutes.
[0103] The method for preparing the test electrochemical cell was as follows: First, the working electrode (positive electrode) was prepared by using 10 mg of the VS4 powder obtained in Synthesis Example 1 or the MoS 5.7 To 10 mg of the electrolyte, 1 mg of Ketjen Black and 1 mg of polytetrafluoroethylene (PTFE) as a binder were added, mixed in a mortar for 8 minutes, and then attached to an aluminum mesh to prepare the electrolyte. Lithium metal was used as the counter electrode (negative electrode). Polypropylene was used as the separator. The results of the charge-discharge cycle characteristics of Examples 1 to 4 and Comparative Examples 1 to 2 are shown in FIG. 1, and the charge-discharge efficiency and capacity retention rate at 50 cycles of Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 1. As can be seen from FIG. 1 and Table 1, all of the Examples (capacity retention rate after 50 cycles: 47.9 to 60.0%) showed a higher capacity retention rate than the Comparative Examples (37.1 to 37.6%). Also, as can be seen from Table 1, all of the Examples showed a higher charge-discharge efficiency than the Comparative Examples.
[0104] [Table 1] [Industrial Applicability]
[0105] The nonaqueous secondary battery electrolyte of the present invention and the nonaqueous secondary battery using the electrolyte can be used in various known applications, such as notebook computers, mobile phones, electric vehicles, load leveling power sources, and natural energy storage power sources.
Claims
1. A non-aqueous secondary battery electrolyte, comprising: The nonaqueous secondary battery uses a lithium-free transition metal sulfide as a positive electrode active material, The electrolyte solution contains an organic solvent containing a cyclic carbonate compound, and the content of the cyclic carbonate compound is 80 to 100 volume % and the content of the chain carbonate compound is 0 to 20 volume % relative to the total volume of the organic solvent being 100 volume %, The non-aqueous secondary battery electrolyte, wherein the lithium-free transition metal sulfide is vanadium sulfide.
2. 2. The nonaqueous secondary battery electrolyte according to claim 1, wherein the cyclic carbonate compound is at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate.
3. 3. The non-aqueous secondary battery electrolyte according to claim 1, wherein the chain carbonate compound is at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and methyl propyl carbonate.
4. The electrolyte for a non-aqueous secondary battery described in any one of claims 1 to 3, further containing a lithium salt.
5. 5. The nonaqueous secondary battery electrolyte according to claim 4, wherein the lithium salt is at least one selected from the group consisting of an organic lithium salt having a sulfonyl group, an inorganic lithium salt, and an organic lithium salt having a boron atom.
6. The lithium salt is lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(pentafluoroethanesulfonyl)imide (Li(C 2 F 5 SO 2 ) 2 N), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium perchlorate (LiClO 4 ), lithium bis(oxalato)borate (LiBOB), lithium oxalatodifluoroborate (LiBF 2 (C 2 O 4 )), and lithium bis(malonate)borate (LiB(C 3 O 4 H 2 ) 2 6. The nonaqueous electrolyte solution for a secondary battery according to claim 4, wherein the nonaqueous electrolyte solution for a secondary battery is at least one selected from the group consisting of:
7. The electrolyte for a non-aqueous secondary battery according to claim 4, wherein the concentration of the lithium salt in the electrolyte is 0.3 to 2.0 mol / L.
8. The electrolyte for a non-aqueous secondary battery described in any one of claims 1 to 7, wherein the electrolyte is an electrolyte for a lithium ion secondary battery.
9. A non-aqueous secondary battery comprising the non-aqueous secondary battery electrolyte solution according to any one of claims 1 to 8.
10. 10. The nonaqueous secondary battery according to claim 9, which is a lithium ion secondary battery.
Citation Information
Patent Citations
All-solid-state rechargeable lithium cell
JP2018537813A
Secondary battery
JP2020126769A
Low crystallinity vanadium sulfide
WO2018181698A1
